2022
DOI: 10.3390/biomedicines10102485
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MicroRNAs as Novel Cell-Free Therapeutics in Tissue Engineering and Regenerative Medicine

Abstract: Extracellular vesicles (EVs) are membrane-bound vesicles (50–1000 nm) that can be secreted by all cell types. Microvesicles and exosomes are the major subsets of EVs that exhibit the cell–cell communications and pathological functions of human tissues, and their therapeutic potentials. To further understand and engineer EVs for cell-free therapy, current developments in EV biogenesis and secretion pathways are discussed to illustrate the remaining gaps in EV biology. Specifically, microRNAs (miRs), as a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 175 publications
0
9
0
Order By: Relevance
“…On top of directly utilizing EVs derived from MSCs, there also exist attempts to manipulate the EVs ex vivo in order to facilitate a more optimal therapeutic approach. One of the most used methods for manipulation of EVs includes the modulation of their miRNA content (Yoo et al, 2018;Abreu et al, 2021;Zeng et al, 2022). This is performed by a procedure termed exo-miRNA loading, which is done in one of two ways: 1) producing a cell line over-expressing the desired miRNA or 2) loading EVs with miRNA using chemical or physical methods (Munir et al, 2020).…”
Section: Application Of Extracellular Vesicles Derived From Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…On top of directly utilizing EVs derived from MSCs, there also exist attempts to manipulate the EVs ex vivo in order to facilitate a more optimal therapeutic approach. One of the most used methods for manipulation of EVs includes the modulation of their miRNA content (Yoo et al, 2018;Abreu et al, 2021;Zeng et al, 2022). This is performed by a procedure termed exo-miRNA loading, which is done in one of two ways: 1) producing a cell line over-expressing the desired miRNA or 2) loading EVs with miRNA using chemical or physical methods (Munir et al, 2020).…”
Section: Application Of Extracellular Vesicles Derived From Mscsmentioning
confidence: 99%
“…In addition to direct transplantation of MSCs, there also exist studies researching the application of MSCs' byproducts, such as exosomes (Zeng et al, 2022). For example, a 2021. study by Chen et al has shown that WJ-MSC-derived exosomes loaded with miR-29a, which mainly affects histone deacetylase 4 (HDAC4) (Müller et al, 2016), caused a significant decrease in nuclear HDAC4 (Chen et al, 2021b).…”
Section: Alzheimers' Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Circulating free miRNAs and exomiRs have been proposed as promising non-invasive biomarkers for cancer diagnosis, prognosis, treatment and monitoring of disease progression [ 170 ]. Currently, the potential of exomiRs is being assessed as a novel therapy strategy of cancer and other diseases [ 171 , 172 , 173 ]. In BC, c-miRNAs and exomiRs have been shown to affect essential features such as tumor growth, invasion and angiogenesis [ 174 ].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…They are emerging as key regulators of intercellular communication in health and disease with potential relevance as biomarkers and therapeutic strategies in different pathological conditions [54,55]. EVs can transfer their bioactive cargo from donor to recipient cells and influence the biological function of the target cell.…”
Section: Introductionmentioning
confidence: 99%